Analysis of Students’ Problem-Solving Ability in Solving Science (Physics) Problems in Work Materials and Simple Aircraft Class VIII MTsN 2 Trenggalek - Husni Cahyadi Kurniawan; Siti Fatimah; Ambar Sari (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
This study aims to describe students’ problem-solving abilities and percentages in solving science (physics) problems in Work materials and simple aircraft class VIII MTsN 2 Trenggalek. This research uses a qualitative approach with a descriptive type of research. The data collection techniques used are tests and interviews. The data analysis includes 3 stages: data reduction, data presentation, and conclusion. The results of the research on students’ problem-solving ability are based on the stages of the Polya model: (1) High-ability students have been able to meet all indicators of the Polya problem-solving stages by 82.99% in the very high category. (2) Moderately capable students can already meet all indicators of the problem-solving stages for Work questions. However, they are still less capable in simple aircraft questions, with a percentage of 64.58% being in the high category. (3) Low-ability students have not been able to meet all the indicators of the problem-solving stage, with 15.42% being in the deficient category. Students cannot understand problems, draw plans, execute plans, and look back. The reason is that students do not understand the material clearly, which impacts their problem-solving ability. The research showed that students’ problem-solving ability is in a suitable category with a percentage of 54.33%. The stage of understanding the problem includes the stages the student can achieve. Students are still underprivileged in the following three stages: drawing up a plan, implementing a plan, and looking back. Students still have difficulty determining the right strategy to solve problems in Work and simple aircraft questions.